Enhancing Reading Comprehension Among Informatics Management Students through the Grammarian Android Game: A Classroom Action Research - Romadhon, Romadhon (General English Education, 2024)
This research investigates the effectiveness of the Grammarian Android Game in improving the reading comprehension skills of third-semester Informatics Management students at Piksi Input Serang Polytechnic. The study adopts a Classroom Action Research (CAR) methodology, conducted in two cycles, involving 28 students. Initial observations indicated significant challenges in reading comprehension, with most students scoring below the required competency level. The introduction of the Grammarian Android Game aimed to address these challenges by providing an interactive and engaging learning tool. Results showed substantial improvements in students' reading comprehension scores, increasing from an average of 60.72 in the pre-cycle to 92.21 in the second cycle. The iterative process of planning, acting, observing, and reflecting facilitated continuous improvement in teaching strategies, leading to enhanced student engagement and understanding. The study concludes that the Grammarian Android Game is an effective tool for enhancing reading comprehension, making the learning process more enjoyable and effective. This research contributes to the understanding of digital game-based learning's impact in higher education, particularly in technical fields.